IMPLEMENTASI MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 016 SEKELADI KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Jayarni Jayarni; Eddy Noviana; Lazim. N Lazim. N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study was motivated by the percentage of students who achieve KKM 65 in the second semester 2014/2015 is still low. Of the 20 students, only 8 JV (40.00%) of students who reach KKM and 12 people (60.00%). Teacher are using current instructional model of teaching and learning process in class. Of these problems is necessary to study a class action by applying problem-based learning model. Where the research is at elementary school 016 Sekeladi research subjects are students of class IV of 20 people, boys 12 and 8 women. This study was conducted in two cycles. Data collection instruments in this study was the observation sheet teacher activity, student activity observation sheet and test daily tests. Observations show that the activity of teachers and students has increased. The activities of teachers in the first cycle 73.86% increase in cycle II to 93.17% with an increase of 19:31%. Activity of students in the first cycle increased 65.90% in the second cycle of 90.90% with 25.00% peningkata. The results showed that the learning outcomes of students also increased, the base score with an average of 57.50 increased in the first cycle to 70.00 with an increase of 12.50%, on the second cycle increased to 87.50% with an increase of 17:50. Mastery learning students in the first cycle showed that 75.00% reaching a predetermined KKM, on the second cycle increased menjdi 95.00%. Based on these results it can be concluded that the implementation of Problem Based Learning Model to improve learning outcomes social science learning of elementary school fourth grade students in the school year 2014/2015 016 SekeladiKeywords: problem based learning model, social learning outcomes